A novel mixing method for powder metallurgy copper‐carbon nanotube composites. Issue 7 (20th July 2020) - Özgün, Ö.; Bulut, C.
Abstract: In this study, copper matrix composite materials with different ratios of carbon nanotubes were produced. The biggest problem faced in the production of carbon nanotube‐reinforced composites is that carbon nanotubes do not distribute homogeneously in the matrix. A novel mixing technique was applied to overcome this problem. Hot pressing was used in sample production. A second high‐pressure densification process was applied following the hot pressing process for enhancing the properties. The properties of both the hot‐pressed specimens and the specimens to which a second high‐pressure densification process was applied were characterized with the density measurements, microstructure examinations, and mechanical tests. The microstructure examinations showed that carbon nanotubes could be distributed homogeneously in the copper matrix with the mixing process applied. It was found out that the high‐pressure densification process applied following the hot‐pressing process increased the relative density and thus, all mechanical properties. Abstract : Carbon nanotubes were homogeneously distributed in the copper matrix through the new mixing technique applied. This novel mixing technique will provide significant contribution to the mixing of nano‐dimensional material powders, or material powders with very big differences between their densities.